Immunisation status of children receiving care and support in Wales: a national data linkage study - Grace Bailey (Frontiers in Public Health, 2023)
In the UK, a robust childhood immunisation programme ensures children are offered protection against serious infections; identifying inequalities in vaccination coverage is essential. This is one of the first data linkage studies to examine coverage of primary, as well as pre-school booster and second dose of MMR vaccines, in children receiving support from social care services across Wales.Methods: By accessing records held within the Secure Anonymised Information Linkage (SAIL) Databank, vaccination status of children receiving social care and support between April 2016 and March 2021 (n = 24,540) was ascertained. This was achieved through linkage of the Children Receiving Care and Support (CRCS) Census and National Community Child Health Database which holds vaccination records for all children in Wales registered for NHS care. This sample was split into three groups – those children who had never been recorded on the Child Protection Register (CPR) or as ‘Looked After’ but in CRCS (n = 12,480), children ever on the CPR (n = 6,225) and those ever recorded as ‘Looked After’ but who were never on the CPR (n = 5,840). The comparison group of children and young people (CYP) never receiving welfare support consisted of 624,905 children.Results: Children receiving care or support were more likely to be up-to-date with all six vaccines (no recorded vaccines: 0.6–6.3%) compared to children in the comparison group (no recorded vaccines: 3–10.3%). However, of those who were vaccinated, they were less likely to be vaccinated in a timely manner; both early (5.2% vs. 22.2%; margin of error [ME] = 0.52, 95% CI [confidence interval] = −0.18 – −0.17, p < 0.001) and delayed vaccinations were more common (62.7% vs. 71.3%; ME = 0.58, 95% CI = 0.08–0.09, p < 0.001). Validation of the CRCS immunisation flag showed moderate levels of accuracy. Around 70% of immunisation flags were correct across all three groups.Discussion: Findings suggest a positive association between receiving services under a care and support plan and being up-to-date with immunisations; children receiving support under a care and support plan were more likely to have experienced early or late vaccinations, demonstrating that there is still more inter-disciplinary co-ordination and planning needed to improve these outcomes. Thus, identifying inequalities in vaccination coverage is essential to target interventions and to prioritise geographic areas for catch-up.